2007
DOI: 10.1080/02786820701203215
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of Selected Dicarboxylic and ω-Oxocarboxylic Acids in Ambient Aerosol to them/z44 Signal of an Aerodyne Aerosol Mass Spectrometer

Abstract: The Aerodyne aerosol mass spectrometer (AMS) employs flash vaporization (600 • C) followed by 70-eV electron impact ionization (EI) to detect organic and inorganic aerosols. The signal at mass-to-charge ratio (m/z) 44 (mainly CO + 2 ) is considered the most reliable marker of oxygenated organic aerosol. This study is the first to evaluate the contribution of selected low molecular weight dicarboxylic acids (diacids) and ω-oxocarboxylic acids (ω-oxoacids) to the particle-phase m/z 44 signal of the AMS mass spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
113
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 104 publications
(129 citation statements)
references
References 25 publications
10
113
1
Order By: Relevance
“…Relationships between m/z 44 and measurements of a few individual organic acids (rather than total particlephase acids) have also been observed in laboratory and field measurements [Takegawa et al, 2007;Sorooshian et al, 2010;Duplissy et al, 2011]. Takegawa et al [2007] observed good correlation (r 2 = 0.85-0.94) between m/z 44 and select dicarboxylic and ω-oxocarboxylic acids collected on filters in Tokyo, Japan.…”
Section: /2015gl064650mentioning
confidence: 67%
See 1 more Smart Citation
“…Relationships between m/z 44 and measurements of a few individual organic acids (rather than total particlephase acids) have also been observed in laboratory and field measurements [Takegawa et al, 2007;Sorooshian et al, 2010;Duplissy et al, 2011]. Takegawa et al [2007] observed good correlation (r 2 = 0.85-0.94) between m/z 44 and select dicarboxylic and ω-oxocarboxylic acids collected on filters in Tokyo, Japan.…”
Section: /2015gl064650mentioning
confidence: 67%
“…Takegawa et al [2007] observed good correlation (r 2 = 0.85-0.94) between m/z 44 and select dicarboxylic and ω-oxocarboxylic acids collected on filters in Tokyo, Japan. Assuming that one of the carboxylic acid groups is detected as the CO 2 + ion, they noted that the measured diacids and oxoacids accounted for 14 ± 5% of the m/z 44 signal in ambient aerosol.…”
Section: /2015gl064650mentioning
confidence: 92%
“…The thermodynamic parameters for these compounds were taken from the Chemical Dictionary (1994). The experimental apparatus was the same as that described by Takegawa et al (2007). The high voltage applied to the QMS detector (electron multiplier) was properly adjusted so that the m/z 39 signal was not saturated.…”
Section: Possible Origins Of Alkali Metal Signalsmentioning
confidence: 99%
“…Takegawa et al (2007) estimated the average ratio of m/z 28 to m/z 44 to be 1.0 for Tokyo data during the summer of 2003 using particle time-of-flight data (P-ToF), in which m/z 28 signals from N + 2 and organics can be separated. Here we estimated the m/z 28 signal from organics using the same method as Takegawa et al (2007). We selected time periods with moderately or very high loadings of OM (11 cases for PRD and 15 cases for CAREBEIJING) and calculated the m/z 28 and 44 signals from organics using the P-ToF data.…”
Section: Aerodyne Aerosol Mass Spectrometer (Ams)mentioning
confidence: 99%
See 1 more Smart Citation